Analysis of Sponsorships in Clubs Participating in NBB 2020-2021 - Edson Hirata; João Paulo Melleiro Malagutti; Fernando Augusto Starepravo2; Felipe Canan (Universidade Salgado de Oliveira, 2021)
The lack of data on sports sponsorship and on the segments that invest the most in this practice, combined with the scarce academic literature on the subject, the lack of professionalism of a large portion of sports managers in Brazil and the lack of knowledge of sponsors about the benefits of sports sponsorship motivated the carrying out of this study, which aimed to analyze the number of sponsors of clubs participating in the NBB 2020-2021, identify the area of activity of their sponsors and which areas were predominant. The research had an exploratory and descriptive nature and used a documental procedure and quantitative analysis. Sponsor data was collected from the official websites and social networks of the 16 clubs participating in the NBB 2020- 2021 season. The data showed a total of 163 sponsoring/supporting companies in total, that is, each team, on average, had 10.2 sponsoring companies. Two diametrically opposite ways emerged for clubs to relate to their sponsors. On the one hand, some teams show a significantly higher number than the average, in the case of Franca (27 companies), Bauru (23), Campo Mourão (21) and Unifacisa (16), and on the opposite side, some teams showed a good number of commercial partners. below average, such as: Corinthians (no company), Pinheiros (2), Paulistano and Minas Tênis (3). These results show heterogeneity in the strategy of clubs participating in the NBB 2020-2021 to relate to this form of revenue. While most basketball clubs have pulverized their partnerships, data show that socio-sports clubs and football clubs are more restrictive when carrying out their commercial partnerships related to sponsorship. The results can be useful for club directors to understand which segments have the greatest potential for interest in the sport, such as the retail trade, health, financial services and education sectors. The results may also indicate to some economic segments that basketball teams are potential possibilities for publicizing the company, given the existence of a significant number of companies in their area among the current sponsors, that is, companies belonging to the areas mentioned above should be on the lookout for opportunities to connect with sports sponsorship through basketball, as your competitors appeared more frequently in this survey.